Creating Synergies between Citizen Science and Indigenous and Local Knowledge. (28th April 2021) - Tengö, Maria; Austin, Beau J; Danielsen, Finn; Fernández-Llamazares, Álvaro
Abstract: Citizen science (CS) is receiving increasing attention as a conduit for Indigenous and local knowledge (ILK) in ecosystem stewardship and conservation. Drawing on field experience and scientific literature, we explore the connection between CS and ILK and demonstrate approaches for how CS can generate useful knowledge while at the same time strengthening ILK systems. CS invites laypersons to contribute observations, perspectives, and interpretations feeding into scientific knowledge systems. In contrast, ILK can be understood as knowledge systems in its own right, with practices and institutions to craft legitimate and useful knowledge. Such fundamental differences in how knowledge is generated, interpreted, and applied need to be acknowledged and understood for successful outcomes. Engaging with complementary knowledge systems using a multiple evidence base approach can improve the legitimacy of CS initiatives, strengthen collaborations through ethical and reciprocal relationships with ILK holders, and contribute to better stewardship of ecosystems.